Modeling of team competence management in the digital network space of crisis management centres of the EMERCOM of Russia: on the way to the digital twin - E. N. Kulishov (Цифровая социология)
The article discusses issues related to modeling of social processes of team competence management in the digital network space of the crisis management centres (hereinafter referred to as CMC) of the Ministry of the Russian Federation for Civil Defence, Emergencies and Elimination of Consequences of Natural Disasters (hereinafter referred to as EMERCOM of Russia). It is done on the example of the CMC of the three institutions: State Fire Service of the EMERCOM of Russia (Moscow), the Civil Defense Academy of the EMERCOM of Russia (Khimki) and the Main Directorate of the EMERCOM of Russia in Sevastopol. A brief description of the digital environment of the CMC is given (a typical scheme). This problem is considered from the perspective of active use in modeling of the concept of an integrative competence approach focused on actions (T. Parsons’ structural and functional approach). The knowledge parameters scheme used in the analysis of competencies is proposed. The sociology of management and the sociology of small groups allow us to study processes that ensure stability of social systems-communities in the form of work teams with specific social relationships and conditions manifesting primarily as “cognitive blockades”, psychological burnouts, etc. The research presents the results of a sociological analysis on the formation of a system of indicators characterising effectiveness of the work of teams of the CMC while analysing emergency situations, forecasting their development and liquidating them. Also, the research gives the results of practical modeling to assess the impact of the competence level on effectiveness and productivity of the teams of the CMC using cognitive models the formation of which happens in accordance with the concept of structural and targeted analysis. Such cognitive models characterise individual patterns of behaviour of duty shifts in emergency situations and are one of the elements that participate in the development of digital twins of the teams